2019
DOI: 10.3390/diagnostics9030109
|View full text |Cite
|
Sign up to set email alerts
|

Value and Diagnostic Efficacy of Fetal Morphology Assessment Using Ultrasound in a Poor-Resource Setting

Abstract: Background: Ultrasound is operator-dependent, and its value and efficacy in fetal morphology assessment in a low-resource setting is poorly understood. We assessed the value and efficacy of fetal morphology ultrasound assessment in a Nigerian setting. Materials and Methods: We surveyed fetal morphology ultrasound performed across five facilities and followed-up each fetus to ascertain the outcome. Fetuses were surveyed in the second trimester (18th–22nd weeks) using the International Society of Ultrasound in O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…These results fall in line with Anderson et al (1995) who proposed that the CNS was reported in 92% of the CAs and Singh et al (2006) who concluded that the common anomaly was ventriculomegaly 27.33% followed by anencephaly 26.00%. Although other authors (Ukweh et al, 2019) stated that a majority (35%) of the detected CAs were related to the central nervous system followed by digestive (12.8%) and genitourinary (11.9%) systems.…”
Section: Asymptomaticmentioning
confidence: 84%
See 1 more Smart Citation
“…These results fall in line with Anderson et al (1995) who proposed that the CNS was reported in 92% of the CAs and Singh et al (2006) who concluded that the common anomaly was ventriculomegaly 27.33% followed by anencephaly 26.00%. Although other authors (Ukweh et al, 2019) stated that a majority (35%) of the detected CAs were related to the central nervous system followed by digestive (12.8%) and genitourinary (11.9%) systems.…”
Section: Asymptomaticmentioning
confidence: 84%
“…Onyambu and Tharamba (2018) showed that the prevalence of CAs through routine U/S was 3%. Ukweh et al (2019) concluded that anomaly prevalence is 1.67%. Neto et al (2009) indicated a very high prevalence of CAs; they stated that the prenatal ultrasonography diagnosed congenital anomalies presented in 63.2%, among this 56.2% were confirmed after birth.…”
Section: Asymptomaticmentioning
confidence: 99%
“…“Scanning errors” (also called “search errors”) result from failures in the first stage of search. Specifically, peripheral information fails to guide the observer's gaze to a relevant location, and high-resolution foveal vision does not assist interpretation because the observer never looks at the location directly ( Doshi et al, 2019 ; Holland, Sun, Gackle, Goldring, & Osmar, 2019 ; Ukweh, Ugbem, Okeke, & Ekpo, 2019 ). In “recognition errors,” abnormalities are foveated too briefly for the observer to correctly recognize them ( Holland et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%